Scale effect on ship resistance components and form factor - Dogrul, Ali; Song, Soonseok; Demirel, Yigit Kemal (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
To design eco-friendly ships, the hydrodynamic behaviour of the hull has to be estimated precisely. The first and foremost one is the ship resistance, which is closely related to the energy efficiency of the ship. Different extrapolation methods, based on different assumptions, have been used to predict the full-scale ship resistance from model-scale experiments. In this manner, it is important to understand the scale effect on the individual ship resistance components. In this study, URANS CFD simulations of KCS and KVLCC2 were conducted at different scales. The total resistance components were decomposed into the individual resistance components to investigate the scale effects. The simulation results were compared with full-scale resistance predictions using different extrapolation methods and the rationale of the different compliances between them was investigated. Finally, the hydrodynamic characteristics in different scales were examined.
Keywords: CFD; Ship resistance; Scale effect; KCS; KVLCC2; Form factor; NOMINAL WAKE; MODEL; Engineering; Oceanography